Smart Door Lock Innovation Using Integration of Bluetooth Low Energy and MQTT IoT Protocol - Kurniasyah, Ikmal; Rakhmawati, Lusia (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2025)
This research develops a smart door lock system using ESP32 with Bluetooth Low Energy (BLE) and MQTT IoT protocol integration to ensure secure and efficient access control. The system supports RFID, fingerprint, and keypad authentication, with BLE utilized for device detection and proximity validation. Testing results show optimal performance, with MQTT QoS 0 achieving the highest throughput (5,052 kbps) and lowest delay (175 ms), while QoS 2 offers superior stability and minimal jitter (19 ms). RSSI analysis confirms the impact of distance and interference on BLE signal quality. The system reliably prevents unauthorized access and ensures real-time monitoring, making it suitable for modern security applications. Keywords: Smart door lock, ESP32, Bluetooth Low Energy, MQTT IoT, RSSI